The Changing Terrain of Religious Freedom - Adcock, Cassie; Arriaga, Kristina; Balmer, Randall; Baraka Thomas, Jolyon; Beaman, Lori G; Bielefeldt, Heiner; Green, Jeffrey E. 1974-; Green, Jeffrey E. 1974-; Matz, Joshua; Philpott, Daniel; Schmidt, Leigh E; Schultz, William; et al. (Philadelphia University of Pennsylvania Press, 2021)
Frontmatter -- Contents -- Introduction: The Landscape of Religious Freedom -- Part I. Ethical Arguments -- 1. A Right of Its Own: A Case for the Human Right of Religious Freedom -- 2. Can Freedom of Religion or Belief (FoRB) Be Universal? -- Part II. The Social Contingency of Religious Freedom Disputes -- 3. Microclimates of Religious Freedom: Global Norms Meet Local Conditions in Territorial Hawai`i and Occupied Japan -- 4. The Protection of Religion as “Culture” and “History”: Three Case Studies -- 5. “Baptism of Ire”: Atheist Plaintiffs and Irreligious Freedom in Postwar America -- 6. The Heads or Tails of Cow Protection in India: Religious Freedom and Secular Agriculture -- 7. Bad Faith: Religious Fraud and Religious Freedom in the “Mighty I AM” Case -- Part III. The (Mis)application of Religious Freedom -- 8. The Historian’s Pickaxe: Uncovering the Racist Origins of the Religious Right -- 9. Female Genital Cutting in Michigan: How Advocates of the Dawoodi Bohra Distorted Religious Freedom to Control Women’s Sexual Conduct -- 10. The U.S. Supreme Court and the Future of Religious Freedom in the United States -- Notes -- Contributors -- Index -- Acknowledgments
The Changing Terrain of Religious Freedom offers theoretical, historical, and legal perspectives on religious freedom, while examining its meaning as an experience, value, and right. The volume starts from the premise that the terrain of religious freedom has never been easy and smooth. Across societies and throughout history, defending or contesting principles of religious freedom has required compromise among multiple interests, balancing values, and wrangling with the law.Drawing on examples from the United States and around the world, and approaching the subject from the disciplines of history, law, sociology, philosophy, religious studies, and political science, the essays in this volume illustrate these challenges. They sketch the contours of contemporary debates while showing how the landscape of religious freedom has shifted over time. They consider various stakeholders that have asserted competing claims, among them individuals and groups; members of minority and majority communities; states and corporations (including both religious organizations and businesses); and believers and non-believers. Taken together, the studies in this volume suggest that understanding religious freedom means grappling with conflicting and perhaps irreconcilable claims about whose rights should prevail over others, what religion is or may be, and how religion should relate to other cultural values
[Online-Ausgabe]
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: POLITICAL SCIENCE / Human Rights; Atheism; Church and State; Constitutional law; Freedom of conscience; Human rights; Racism and Religious Right; Religion and politics; Religion; Religious Freedom and the Supreme Court; Religious freedom; Religious liberty; Unbelief; Universal rights